Using multiple data types and integrated population models to improve our knowledge of apex predator population dynamics. Issue 22 (11th October 2017) - Bled, Florent; Belant, Jerrold L.; Van Daele, Lawrence J.; Svoboda, Nathan; Gustine, David; Hilderbrand, Grant; Barnes, Victor G.
Abstract: Current management of large carnivores is informed using a variety of parameters, methods, and metrics; however, these data are typically considered independently. Sharing information among data types based on the underlying ecological, and recognizing observation biases, can improve estimation of individual and global parameters. We present a general integrated population model (IPM), specifically designed for brown bears ( Ursus arctos ), using three common data types for bear ( U . spp.) populations: repeated counts, capture–mark–recapture, and litter size. We considered factors affecting ecological and observation processes for these data. We assessed the practicality of this approach on a simulated population and compared estimates from our model to values used for simulation and results from count data only. We then present a practical application of this general approach adapted to the constraints of a case study using historical data available for brown bears on Kodiak Island, Alaska, USA. The IPM provided more accurate and precise estimates than models accounting for repeated count data only, with credible intervals including the true population 94% and 5% of the time, respectively. For the Kodiak population, we estimated annual average litter size (within one year after birth) to vary between 0.45 [95% credible interval: 0.43; 0.55] and 1.59 [1.55; 1.82]. We detected a positive relationship between salmon availability and adult survival, with survival probabilities greater for females than males. Survival probabilities increased from cubs to yearlings to dependent young ≥2 years old and decreased with litter size. Linking multiple information sources based on ecological and observation mechanisms can provide more accurate and precise estimates, to better inform management. IPMs can also reduce data collection efforts by sharing information among agencies and management units. Our approach responds to an increasing need in bear populations' management and can be readily adapted to other large carnivores. Abstract : We present an integrated population model (IPM) using three common data types for bear ( Ursus spp.) populations: repeated counts, capture‐mark‐recapture (CMR), and litter size. We successfully assessed the practicality of this general approach on a simulated bear population and then compared a subset of our model to data available for brown bears ( U. arctos ) on Kodiak Island, Alaska, USA, with results consistent with literature. We conclude that linking multiple information sources based on ecological and observation mechanisms can provide more accurate and precise population estimates to better inform management.